2020
DOI: 10.2981/wlb.00596
|View full text |Cite
|
Sign up to set email alerts
|

Constraints to hunting and harvesting elk in a landscape dominated by private land

Abstract: While the harvest success rate of bull elk in Nebraska has been relatively high in recent years, antlerless harvest success is substantially lower inhibiting the ability of wildlife managers to effectively manage population numbers. We sought to explore differences in hunter behaviour based on the type of elk being hunted as well as how specific constraints affected each type of hunter's ability to hunt and harvest elk. Decreased antlerless‐elk harvest rates were likely a product of the reduced frequency in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Our results suggested that land access and conflict with other hunters were generally some of the relatively stronger constraints, with waterfowl hunters rating them as more limiting. Waterfowl hunters (current and former) and non‐waterfowl hunters and anglers tended to view (1) asking for permission, (2) crowding, (3) knowing who to ask for permission, and (4) obtaining permission as impediments to hunting waterfowl, which is consistent with previous research of hunters (Backman and Wright 1993, Montgomery and Blalock 2010, Metcalf et al 2015, Gruntorad and Chizinski 2020). Further, frequent and sporadic waterfowl hunters viewed these as relatively stronger constraints but it did not prohibit them from participating in their activity, which suggests that they have successfully negotiated these impediments (Kay and Jackson 1991, Shaw et al 1991) or had the motivations to do so (Jackson et al 1993).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results suggested that land access and conflict with other hunters were generally some of the relatively stronger constraints, with waterfowl hunters rating them as more limiting. Waterfowl hunters (current and former) and non‐waterfowl hunters and anglers tended to view (1) asking for permission, (2) crowding, (3) knowing who to ask for permission, and (4) obtaining permission as impediments to hunting waterfowl, which is consistent with previous research of hunters (Backman and Wright 1993, Montgomery and Blalock 2010, Metcalf et al 2015, Gruntorad and Chizinski 2020). Further, frequent and sporadic waterfowl hunters viewed these as relatively stronger constraints but it did not prohibit them from participating in their activity, which suggests that they have successfully negotiated these impediments (Kay and Jackson 1991, Shaw et al 1991) or had the motivations to do so (Jackson et al 1993).…”
Section: Discussionsupporting
confidence: 87%
“…Yet, increasing public land access is challenging and not easily accomplished by agencies. Alternatives to purchasing more land such as leasing or obtaining permission on private property to disperse hunters on the landscape is needed (Gruntorad and Chizinski 2020, Wszola et al 2020 b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By 1997, there was ≈150 elk and permanent hunting seasons were instituted in 1995. The Game and Parks Commission had established seven Elk Management Units (EMU) in the western half of Nebraska by 2008, which are still in use today (Gruntorad and Chizinski 2020). Our two sight records are of individuals that have been observed to the east of the EMU in the last 10 years, indicating this highly mobile species is still in the process of re-establishing populations statewide as they were in pre-settlement times.…”
Section: Cervus Canadensis Nelsonimentioning
confidence: 83%
“…Hunting participation has been steadily declining over the past 2 decades (Mozumder et al 2007, Ryan and Shaw 2011, Vrtiska et al 2013, Larson et al 2014, Bureau of the Census and United States Fish and Wildlife Service 2018) and constitutes a threat to wildlife conservation and management in North America (Enck et al 2000, Li et al 2003). State agencies concerned over reduced hunter numbers are increasingly investing in efforts to better understand their constituents (Gruntorad and Chizinski 2020, Hinrichs et al 2020, Wszola et al 2020 a , b ) and assessing shifting demographics of hunter participation (Vaske and Manfredo 2012, Keogh George 2016, Rodriguez et al 2016). To help offset the consequences associated with the decline in hunters, wildlife agencies and non‐governmental organizations have expended considerable time, money, and effort to increase hunter participation through recruitment, retention, and reactivation (R3) programs (Metcalf et al 2015, Council to Advance Hunting and the Shooting Sports 2016).…”
Section: Elk Hunting In Nebraskamentioning
confidence: 99%